Confirming the thermal Comptonization model for black hole X-ray emission in the low-hard state - Castro, M.; D'Amico, F.; Braga, J.; Maiolino, T.; Pottschmidt, K.; Wilms, Jörn (Astronomy & Astrophysics, 2014)
Hard X-ray spectra of black hole binaries in the low/hard state are well modeled by thermal Comptonization of soft seed photons by a corona-type region with kT similar to 50 keV and optical depth around 1. Previous spectral studies of 1E 1740.7-2942, including both the soft and the hard X-ray bands, were always limited by gaps in the spectra or by a combination of observations with imaging and non-imaging instruments. In this study, we have used three rare nearly-simultaneous observations of 1E 1740.7-1942 by both XMM-Newton and INTEGRAL satellites to combine spectra from four different imaging instruments with no data gaps, and we successfully applied the Comptonization scenario to explain the broadband X-ray spectra of this source in the low/hard state. For two of the three observations, our analysis also shows that, models including Compton reflection can adequately fit the data, in agreement with previous reports. We show that the observations can also be modeled by a more detailed Comptonization scheme. Furthermore, we find the presence of an iron K-edge absorption feature in one occasion, which confirms what had been previously observed by Suzaku. Our broadband analysis of this limited sample shows a rich spectral variability in 1E 1740.7 2942 at the low/hard state, and we address the possible causes of these variations. More simultaneous soft/hard X-ray observations of this system and other black-hole binaries would be very helpful in constraining the Comptonization scenario and shedding more light on the physics of these systems.
Keywords: radiation mechanisms: non-thermal; radiation mechanisms: thermal; X-rays: stars